Design criteria of GaAs on silicon tandem solar cells for terrestrial applications - Aberle, Armin G.; Liu, Haohui; Nobre, André M.; Ren, Zekun; Buonassisi, Tonio; Peters, Ian Marius (Optics InfoBase Conference Papers, 2014)
Design criteria for GaAs on crystalline silicon tandem solar cells under spectral conditions at different locations are presented. Such double-junction solar cells have the potential for realizing commercial PV modules with 1-Sun efficiencies of 30%.
CRIS-Team Scopus Importer:2023-03-07